2015
DOI: 10.1073/pnas.1510516112
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ALIX is required for the endosomal localization of the deubiquitinating enzyme AMSH3

Abstract: Ubiquitination is a signal for various cellular processes, including for endocytic degradation of plasma membrane cargos. Ubiquitinating as well as deubiquitinating enzymes (DUBs) can regulate these processes by modifying the ubiquitination status of target protein. Although accumulating evidence points to the important regulatory role of DUBs, the molecular basis of their regulation is still not well understood. Associated molecule with the SH3 domain of signal transduction adaptor molecule (STAM) (AMSH) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 69 publications
5
64
0
Order By: Relevance
“…Erika Isono (University of Konstanz, Germany) reported that the SH3 domaincontaining protein 2 (SH3P2) that is present in CCVs is an ubiquitinbinding protein that can interact with both the deubiquitylating enzyme associated molecule with the SH3 domain of STAM3 (AMSH3) and ESCRT-I (Nagel et al, 2017). In addition, AMSH3 function is regulated by apoptosis-linked gene-2 interacting protein X (ALIX) (Kalinowska et al, 2015), which suggests that SH3P2, AMSH3, ESCRT-I and ALIX function together to send ubiquitylated cargos for degradation through the ESCRT pathway.…”
Section: Escrt Complexesmentioning
confidence: 99%
“…Erika Isono (University of Konstanz, Germany) reported that the SH3 domaincontaining protein 2 (SH3P2) that is present in CCVs is an ubiquitinbinding protein that can interact with both the deubiquitylating enzyme associated molecule with the SH3 domain of STAM3 (AMSH3) and ESCRT-I (Nagel et al, 2017). In addition, AMSH3 function is regulated by apoptosis-linked gene-2 interacting protein X (ALIX) (Kalinowska et al, 2015), which suggests that SH3P2, AMSH3, ESCRT-I and ALIX function together to send ubiquitylated cargos for degradation through the ESCRT pathway.…”
Section: Escrt Complexesmentioning
confidence: 99%
“…Plantspecific substitutes for this subunit could be several ubiquitin receptors in the early endocytic pathway of plants (Mosesso et al, 2019). In Arabidopsis the conserved scaffolding protein, apoptosis-linked gene-2 interacting protein X (ALIX), binds membranes, ubiquitin, and K63-linked ubiquitin chains, and interacts with Vacuolar Sorting Protein 23A (VPS23A) and FYVE1 (Fab1, YOTB, Vac1, and EEA1)/FREE1 (FYVE DOMAIN PROTEIN REQUIRED FOR ENDOSOMAL SORTING 1), essential for ESCRT-I as well as ESCRT-III function (Cardona-Lopez et al, 2015;Kalinowska et al, 2015;Shen et al, 2018). The plantspecific FYVE1/FREE1 localizes to MVBs and binds ubiquitin as well as PtdIns(3)P, and furthermore interacts with the Src homology-3 (SH3) domain-containing protein 2 (SH3P2), VPS23A/B, and the ESCRT-III complex (Barberon et al, 2014;Gao et al, 2014;Kolb et al, 2015;Belda-Palazon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Only few ubiquitin receptors functioning in the vacuolar degradation pathway of plants have so far been characterized (Spitzer et al, 2006;Gao et al, 2014;Kalinowska et al, 2015;Nagel et al, 2017;Wang et al, 2017), and the functionality of their UBDs and their regulation have not been assessed. Eukaryotic PM-borne ubiquitin receptors that have been reported, such as E/ANTH endocytic receptors, do not contain conserved UBDs in plants (Holstein and Oliviusson, 2005), indicating that ubiquitinated cargoes need to be recognized by other PMlocalized ubiquitin receptors Nagel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis has one ALIX homologue, which has the same domain structure as the mammalian ALIX and yeast Bro1 (Table 1). The structure of these proteins comprises an N-terminal Bro1 domain, a V-shaped domain and a C-terminal proline-rich domain (PRD) (Cardona-Lopez et al, 2015;Kalinowska et al, 2015). Although the sequence identity between orthologues is only ∼20%, the organisation of their protein domains is identical.…”
Section: Tom1-like Proteins Are Ub Adaptor Proteins Expanded In Plantsmentioning
confidence: 99%